2013
DOI: 10.4049/jimmunol.1201908
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Expression, and Functional Characterization of TL1A-Ig

Abstract: TNF superfamily member 15 (TL1A) is the ligand for TNFR superfamily (TNFRSF)25. We previously reported that TNFRSF25 stimulation with an agonist Ab, 4C12, expands pre-existing CD4+Foxp3+ regulatory T cells (Tregs) in vivo. To determine how the physiological ligand differs from the Ab, we generated a soluble mouse TL1A-Ig fusion protein that forms a dimer of TL1A trimers in solution with an apparent molecular mass of 516 kDa. In vitro, TL1A-Ig mediated rapid proliferation of Foxp3+ Tregs and a population of CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 50 publications
1
46
0
1
Order By: Relevance
“…Recently, it was reported that murine TL1a-Ig fusion protein expanded preexisting Tregs in vivo. 44 On the other hand, it was also reported that the binding of TL1a to DR3 expressed on human T cells caused increased IFNg production and promoted Th1 differentiation in vitro. 45,46 Our data suggest that the major effects of the activation of DR3 signaling in vivo were caused by the expansion and activation of Tregs in donor mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that murine TL1a-Ig fusion protein expanded preexisting Tregs in vivo. 44 On the other hand, it was also reported that the binding of TL1a to DR3 expressed on human T cells caused increased IFNg production and promoted Th1 differentiation in vitro. 45,46 Our data suggest that the major effects of the activation of DR3 signaling in vivo were caused by the expansion and activation of Tregs in donor mice.…”
Section: Discussionmentioning
confidence: 99%
“…Tnfsf15 −/− mice show disease severity in antigen-induced arthritis (Bull et al, 2008; Wang et al, 2013). DR3 activation either by agonistic antibody (4C12) (Schreiber et al, 2010), TL1A-Ig fusion protein (Khan et al, 2013), or TL1A transgenic mouse, induces Treg cell expansion. Two studies using TL1A transgenic mice reported that the engagement of DR3 on Treg cells dampens their suppressive function and exacerbates inflammation (Meylan et al, 2011; Taraban et al, 2011).…”
Section: The 1p36 Cosignaling Tnf Receptorsmentioning
confidence: 99%
“…The published data showed expansion of CD4+CD25+Foxp3+ cells in the context of co-stimulation or vaccination with a peak value at 5 to 6 days which was the half-life of the antibodies (Schreiber et al 2010 and 2012, Wolf et al 2012, Khan et al 2013). Thus, the possible expansion of antigen specific Tregs cells with this type of co-stimulation with DNA Aβ42 immunization prompted us to further characterize the T cell site.…”
Section: Introductionmentioning
confidence: 99%